ANALISIS KESESUAIAN PRASYARAT KAMPUNG SASARAN DENGAN KAMPUNG TERAPAN TERHADAP PROGRAM POLA PENANGANAN PERMUKIMAN KUMUH PERKOTAN DI INDONESIA - Jauhari Effendi; Sudirman S Sudirman S (Environmental Research Center (PPLH) of Udayana University, 2012)
This study aim to analyze concordance of target kampong prerequisite with applied kampong from result of execution of 4 project of settlement handling pattern of urban which has been executed in Indonesia (KIP, P2KP, CoBILD, and NUSSP). In this study takes 4 samples of dirty settlement in 2 metropolitans town in Indonesia, Penjaringan Kampong (Jakarta) through KIP, while 3 between of location in Makassar City (Sulsel), Ballaparang Kampong (P2KP), Cambayya Kampong (CoBILD), and Rappokalling Kampong ( NUSSP). Primary survey is done by means of assists questionaire to obtain condition of applied kampong reality becoming case for every handling pattern, and situation success of repair component in every handling pattern. Responder is leader RT/RW, prominent public, member of the existing kampong and member of former case kampong which populating has outside case kampong assumed knows initial condition of the kampong. This study applies technique snowballing causing is obtained a number of purposive sample from third kinds of the responder. Result of study indicates that fourth of program which has been executed this generally there is unconformability between conditions signed for target kampong with initial condition of applied kampong. Unconformability between conditions of target kampongs with condition of applied kampong reality, indicates that handling pattern of urban slump which has been executed from year to year has not fully experiences change of condition of happened during the period as according to execution time of the handling pattern.